Gender differences in prosocial tendencies of convicted murderers - Bindasova, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The study is devoted to the study of prosocial tendencies in criminals convicted of murder: various components of empathy, types of assistance depending on the situation, assimilation of social norms of assistance. The sample consisted of convicts serving sentences for intentional unlawful deprivation of another person’s life (murder) aged 19 to 72 years (150 men and 150 women). It was found that men have a higher level of altruistic type of prosocial behaviour than women; women have higher rates of cognitive empathy, fantasy, empathic care and personal distress; men differ from women in high rates of social responsibility and reciprocity norms, the cost – reward norm is significantly higher in women.